Silicon-carbon composite material, preparation method thereof and lithium ion battery

By adsorbing and cracking silane gas on porous carbon to generate elemental silicon, the preparation process of silicon-carbon composite materials is simplified, the complex problems of existing processes are solved, and the electrochemical performance of the negative electrode materials of lithium-ion batteries is improved.

CN119812247APending Publication Date: 2025-04-11ZHEJIANG ZHONGNING SILICON INDUSTRY CO LTD

Patent Information

Application Number
CN202411862471.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have complex processes and complex structures during preparation, resulting in relatively complex preparation processes of lithium-ion batteries.

Method used

The preparation process of silicon-carbon composite material is simplified by adsorbing the porous carbon in a silane atmosphere higher than normal pressure and cracking the silane gas during heating treatment.

Benefits of technology

This method reduces the proportion of silicon deposited on the surface of silicon-carbon composite materials, inhibits the direct contact between silicon and electrolyte, is conducive to the formation and stability of SEI film, and improves the first discharge specific capacity, first effect and capacity retention rate of silicon-carbon negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812247A_ABST
    Figure CN119812247A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite material, a preparation method thereof and a lithium ion battery, and belongs to the technical field of alkali metal ion secondary batteries. The preparation method of the silicon-carbon composite material comprises the following steps: 1) adsorbing silane gas by using porous carbon in a silane atmosphere higher than normal pressure to obtain porous carbon adsorbed with silane; and 2) heating the porous carbon adsorbed with the silane, so that the silane gas adsorbed by the porous carbon is cracked to generate monatomic silicon which is deposited on the porous carbon. According to the preparation method of the silicon-carbon composite material disclosed by the invention, the amount of silicon deposited on the surface of porous carbon can be greatly reduced, so that direct contact between silicon and an electrolyte is reduced, formation of an SEI (Solid Electrolyte Interface) film and improvement of stability are facilitated, and performances such as the first discharge specific capacity, the first efficiency and the capacity retention ratio of the silicon-carbon negative electrode material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method thereof, and a lithium ion battery, belonging to the field of alkali metal ion secondary batteries. Background Art

[0002] Lithium-ion batteries have long been hailed as one of the most popular rechargeable batteries due to their high energy density and long cycle life. At present, graphite, as a normalized negative electrode material for lithium-ion batteries, can no longer meet the needs of equipment due to its low energy density (200-300Wh / kg). In response to this, people have turned their attention to silicon-based negative electrode materials. Silicon has abundant reserves and low cost. It can increase the energy density of batteries by storing more lithium ions. After alloying and storing lithium, the theoretical specific capacity of silicon can reach 4200mAh / g. However, the high volume expansion rate of silicon negative electrode after lithium insertion (about 320%) limits the further commercial use of silicon-based negative electrode materials. After the expansion and rupture of silicon negative electrode, a new electrolyte / active material interface will be introduced, and the electrolyte will continue to be consumed to form a solid electrolyte membrane (SEI membrane), resulting in the pulverization of active materials, destruction of electrode structure and loss of electrical contact, thereby causing rapid decay of battery capacity. In addition, silicon, as a semiconductor material, often has low electronic conductivity, resulting in poor rate performance. Therefore, the development of silicon-based negative electrodes with low expansion effect and higher conductivity has high research and commercial value.

[0003] At present, the treatment of silicon-based negative electrode materials mainly involves nano-sizing silicon and compounding it with porous carbon materials. Since the diffusion rate of lithium ions in solids is slow, nano-sizing silicon can shorten the diffusion distance of lithium ions from the silicon surface to the center, thereby improving the cycle stability and charge and discharge rate. The high specific surface area and excellent electronic and ion conductivity of porous carbon materials make the two highly compatible, and the porous carbon-rich pore structure can inhibit the expansion effect of silicon. For example, the Chinese invention patent application with application publication number CN115995542A and application publication date April 21, 2023 discloses a method for preparing an amorphous silicon-carbon composite material, which is to use a silane cracking method to crack silane substances under high temperature conditions to form nano-silicon particles, and form an amorphous nano-silicon layer on the surface and pores of the porous carbon material. In this scheme, nano-silicon will be deposited on the surface and pores of the porous carbon material. When used as a negative electrode material for lithium-ion batteries, depositing nanosilicon inside the pores of porous carbon materials can buffer the volume expansion generated during charging, protect the contact between silicon and the electrolyte, and is conducive to the formation and stability of the SEI film. The volume expansion of nanosilicon deposited on the surface of porous carbon during charging will have a greater impact on battery performance. In response to this phenomenon, people often use secondary carbon coating to solve the problem. For example, the Chinese invention patent application with application publication number CN113193183A and application publication date July 30, 2021 discloses a method for preparing a high tap density double-carbon layer silicon-carbon composite material. This method uses modified phenolic carbon to coat nanosilicon, and then continues to coat a layer of asphalt carbon on the outer layer to prepare a "double carbon layer" silicon-carbon composite material. When carbon is coated on the surface of the silicon-carbon material again, the volume expansion of nanosilicon on the surface of the porous carbon can be alleviated, effectively preventing nanosilicon from contacting the electrolyte and reducing the occurrence of side reactions. However, this method often requires the addition of a carbon coating process, making the process more complicated. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a silicon-carbon composite material to solve the problem of complex process in the preparation of existing silicon-carbon composite materials.

[0005] The present invention also provides a silicon-carbon composite material prepared by the above preparation method to solve the problem of complex structure of the above existing silicon-carbon composite materials.

[0006] The present invention also provides a lithium ion battery using the silicon-carbon composite material to solve the problem of complex preparation process of lithium ion batteries using existing silicon-carbon composite materials.

[0007] In order to achieve the above objectives, the technical solution adopted by the method for preparing the silicon-carbon composite material of the present invention is: 1) The porous carbon is subjected to adsorption of silane gas in a silane atmosphere at a pressure higher than normal pressure to obtain porous carbon adsorbed with silane; 2) The porous carbon adsorbed with silane is subjected to a heating treatment to decompose the silane gas adsorbed by the porous carbon to generate elemental silicon which is deposited on the porous carbon.

[0008] The preparation method of the silicon-carbon composite material of the present invention utilizes the property that porous carbon can adsorb silane gas, and after the porous carbon adsorbs silane gas to reach adsorption equilibrium, the silane gas is cracked, and the silane gas adsorbed in the pores and on the surface is cracked into silicon element and deposited in situ at the adsorption site; compared with the traditional silane cracking method, the use of this method can reduce the proportion of silicon deposited on the surface of the silicon-carbon composite material, thereby reducing the direct contact between silicon and the electrolyte, which is conducive to the formation and stability of the SEI film, thereby improving the first discharge specific capacity, first efficiency and capacity retention rate of the silicon-carbon negative electrode material. The silicon-carbon composite material prepared by the preparation method of the silicon-carbon composite material of the present invention has a reduced silicon content on the surface, and does not need to be carbon-coated, which can simplify the process while improving the overall performance of the silicon-carbon composite material.

[0009] Preferably, after the adsorption in step 1) is completed, the adsorption amount of silane gas per 10 kg of porous carbon is at least 110 L; the silane gas is monosilane and / or disilane.

[0010] Preferably, the pressure of the silane atmosphere is 0.2-0.6 MPa.

[0011] Preferably, after a certain amount of silane gas is introduced, the porous carbon is subjected to adsorption equilibrium, and the pressure at the adsorption equilibrium is 0.2-0.6 MPa. Thanks to the rich pore structure and unique adsorption characteristics of the porous carbon, the porous carbon is subjected to adsorption equilibrium of silane gas under the above pressure, so that more silane enters the porous carbon pores, and the silicon content on the surface of the silicon-carbon composite material is relatively reduced.

[0012] Furthermore, the BET specific surface area of ​​the porous carbon is 1400-1800 m 2 / g, the average pore size is 2-4nm, and the mesopore ratio is 20-31%. For example, the BET specific surface area of ​​the porous carbon is 1600-1800m 2 / g, and the mesopore accounts for 21-30%. It can be understood that the mesopore refers to a pore with a pore size of 2-50nm.

[0013] Furthermore, the porous carbon is a fruit shell biomass charcoal; the fruit shell biomass charcoal is one or any combination of coconut shell activated carbon, passion fruit shell activated carbon, pecan shell activated carbon, and peanut shell activated carbon. Coconut shell activated carbon is preferred. Biomass charcoal has low cost, and fruit shell biomass charcoal has less ash and higher strength than other types of biomass charcoal. When used in the preparation of silicon-carbon composite materials, it can effectively inhibit the volume expansion effect of silicon.

[0014] Furthermore, the heating treatment is to heat the porous carbon to 600-900° C. for heat preservation. Heat preservation at 600-900° C. can make silane crack better. There is no particular restriction on the time of heat preservation, as long as the adsorbed silane gas can be completely cracked, for example, the time of heat preservation is 10 hours.

[0015] Furthermore, the rate of heating to the insulation treatment temperature is 1-12°C / min, for example, 6°C / min. A suitable heating rate can make the silane cracking in the high temperature range more uniform and stable.

[0016] Furthermore, the adsorption of silane gas by porous carbon and the cracking of silane gas are both carried out in a gas-solid reactor; before the porous carbon adsorbs silane gas, nitrogen gas is first introduced into the gas-solid reactor to replace the atmosphere with an oxygen-free atmosphere, and then silane gas is introduced to form a silane atmosphere. Before the silane gas is introduced, the atmosphere of the gas-solid reactor is replaced with an oxygen-free atmosphere (nitrogen atmosphere).

[0017] In order to increase the proportion of silicon content in the mesopores of the silicon-carbon composite material, the preparation method of the above-mentioned silicon-carbon composite material further includes step 3): returning the porous carbon after the elemental silicon is deposited in step 2) to step 1), and repeating steps 1) and 2) for 2-10 times.

[0018] The technical solution adopted by the silicon-carbon composite material of the present invention is: A silicon-carbon composite material prepared by adopting the preparation method of the silicon-carbon composite material.

[0019] The silicon-carbon composite material of the present invention is prepared by the above-mentioned preparation method of the silicon-carbon composite material, and silicon is deposited in large quantities in the porous structure of the porous carbon, so that when it is used as the negative electrode active material of the alkali metal secondary battery, the first discharge specific capacity, first efficiency and capacity retention rate and other properties can be significantly improved.

[0020] The technical solution adopted by the lithium ion battery of the present invention is: A lithium ion battery uses the silicon-carbon composite material as the negative electrode active material.

[0021] The lithium ion battery of the present invention uses the above silicon-carbon composite material as the negative electrode active material and has a higher first discharge specific capacity, first efficiency and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of a simple experimental device used in a specific embodiment of the present invention to verify that porous carbon has the property of adsorbing silane; Figure 2 1 is a pore size distribution diagram of four types of porous carbon obtained when verifying that the porous carbon has the property of adsorbing silane in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0023] The present invention utilizes the property of porous carbon that can adsorb silane at room temperature, completes the adsorption of silane at room temperature, and then combines the property of high-temperature cracking of silane to prepare silicon-carbon composite materials. Compared with the traditional silane cracking method to prepare silicon-carbon composite materials, the silicon deposition on the surface of porous carbon can be reduced, the direct contact between silicon and electrolyte can be inhibited, and the formation and stability of SEI film can be facilitated.

[0024] The method for preparing the silicon-carbon composite material based on the porous carbon adsorption characteristics comprises the following steps: S1, porous carbon first adsorbs silane under normal temperature in a gas-solid reactor; In this step, before silane is introduced into the gas-solid reactor, nitrogen is introduced into the reactor to replace the air so that the equipment reaches an oxygen-free environment. The flow rate of the silane gas is 5-15 L / min.

[0025] S2, heating the porous carbon after silane adsorption, silane is cracked at high temperature to deposit nano-silicon, and then cooled to room temperature after completion; S3 (optional), steps S1-S2 are repeated 1-10 times to obtain a silicon-carbon composite material.

[0026] The porous carbon is preferably fruit shell biomass carbon, such as one or any combination of coconut shell activated carbon, passion fruit shell activated carbon, pecan shell activated carbon, and peanut shell activated carbon. The preparation methods of the four types of fruit shell activated carbon are as follows: wash the fruit shell raw material and dry it to obtain a dried fruit shell raw material; carbonize the dried fruit shell raw material to obtain fruit shell carbon; crush the fruit shell carbon to obtain fruit shell carbon powder; place the fruit shell carbon powder in a transfer activation furnace, heat it to 550-650°C in a nitrogen atmosphere and keep it warm for 2-3h, then heat it to 700-900°C in a steam atmosphere and keep it warm for 3-4h; crush the dried fruit shell activated carbon crude product and sieve it, heat it to 1000-1500°C in a nitrogen atmosphere, keep it warm for 3-5h, and cool it to obtain the finished fruit shell activated carbon.

[0027] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0028] In order to verify that porous carbon has the property of adsorbing silane, the inventors designed Figure 1 The simple experimental device shown is designed based on the ideal state equation of gas. The experimental steps are as follows: place the porous carbon in a storage tank, turn on the vacuum pump to adjust the pressure to a vacuum state; secondly, turn on the gas bottle switch, adjust the flow meter, use monosilane as the silicon source gas, and introduce a certain amount of monosilane; after the pressure gauge stabilizes at a fixed value (which can be regarded as adsorption reaching equilibrium), open the gas outlet valve to discharge the remaining silane in the tank into the torch for treatment.

[0029] After a certain amount of monosilane is introduced into the storage tank, the pressure gauge pressure rises to the maximum value, named P1. As the adsorption proceeds, the value of the pressure gauge will show a downward trend, indicating that part of the introduced monosilane will be adsorbed by the porous carbon, causing the pressure inside the storage tank to decrease. After the porous carbon has completed the adsorption of monosilane, the value of the pressure gauge will also stabilize. The pressure value at this time is named P2. The amount of monosilane adsorbed by the porous carbon can be roughly calculated through the intermediate pressure difference and the ideal gas state equation, named v. The calculation formula is as follows: Where v is the amount of monosilane adsorbed by porous carbon, unit L, P1-P2 is the pressure difference of the tank after monosilane is adsorbed by porous carbon, unit Pa, V´ is the volume of the tank (fixed at 0.02), unit m 3 , V m is the gas molar volume (fixed at 24.5), unit is L / mol, R is the gas universal constant (fixed at 8.314), unit is J / mol∙K, T is the temperature (fixed at 298.15), unit is K.

[0030] The inventors selected four types of porous carbon from fruit shells, and measured the adsorption of monosilane on each porous carbon according to the above method. During the test, the amount of porous carbon added (10 kg) and the introduction time of monosilane (60 min) were fixed, and the effect of the flow rate of monosilane on the adsorption of monosilane on each porous carbon was further explored by changing the flow rate of monosilane. The test data are shown in Table 1. The pore size distribution diagram of the four porous carbons is shown in Figure 2 As shown, Figure 2 (a)- Figure 2 (d) corresponds to the pore size distribution diagrams of coconut shell activated carbon, passion fruit shell activated carbon, pecan shell activated carbon and peanut shell activated carbon.

[0031] Table 1 Index parameters of porous carbon and the effect of different monosilane flow rates on the adsorption of monosilane It can be seen from Table 1 that coconut shell activated carbon has the most considerable adsorption capacity compared with the other three fruit shell activated carbons.

[0032] 1. Example of Preparation Method of Silicon-Carbon Composite Material Example 1 The method for preparing the silicon-carbon composite material of this embodiment comprises the following steps: 1) Place 10 kg of coconut shell activated carbon in a gas-solid reactor and introduce nitrogen to replace the air in the gas-solid reactor until an oxygen-free environment is formed inside the equipment; 2) After the oxygen-free environment is formed, monosilane is introduced into the gas-solid reactor at a flow rate of 5 L / min. The time for introducing monosilane is 60 min, after which the introduction of monosilane is stopped; 3) After the pressure value of the gas-solid reactor is stable (based on the difference between raw material batches, the time is 2-4 hours and the pressure is 0.2-0.6MPa), the gas-solid reactor is heated at a heating rate of 6°C / min and a heating end point of 600°C. After heating to 600°C, it is kept warm for 10 hours to crack monosilane into elemental silicon, and then cooled to obtain a silicon-carbon composite material.

[0033] Example 2 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 1 only in that the coconut shell activated carbon in step 1) is replaced by passion fruit shell activated carbon.

[0034] Example 3 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 1 only in that the coconut shell activated carbon in step 1) is replaced by pecan shell activated carbon.

[0035] Example 4 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 1 only in that the coconut shell activated carbon in step 1) is replaced by peanut shell activated carbon.

[0036] Example 5 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Embodiment 1 only in that the flow rate of silane in step 2) is 10 L / min.

[0037] Example 6 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Embodiment 1 only in that the flow rate of silane in step 2) is 15 L / min.

[0038] Example 7 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Embodiment 6 only in that the end point of the heating in step 3) is changed to 750°C.

[0039] Example 8 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Embodiment 6 only in that the end point of the heating in step 3) is changed to 900°C.

[0040] Example 9 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 7 only in that: this embodiment adds step 4) on the basis of Example 7): the coconut shell activated carbon after silicon deposition in step 3) is returned to step 2), and steps 2) to 3) are repeated 5 times (i.e., 5 times in total), and the contents not mentioned are the same as those in Example 7.

[0041] Example 10 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 7 only in that: this embodiment adds step 4) on the basis of Example 7): the coconut shell activated carbon after silicon deposition in step 3) is returned to step 2), and steps 2) to 3) are repeated 10 times. The contents not mentioned are the same as those in Example 7.

[0042] Embodiment 11 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Embodiment 7 only in that the silicon source gas in step 2) is changed to disilane.

[0043] Example 12 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 11 only in that: this embodiment adds step 4) on the basis of Example 11): the coconut shell activated carbon after silicon deposition in step 3) is returned to step 2), and steps 2) to 3) are repeated 5 times. The contents not mentioned are the same as those in Example 11.

[0044] Example 13 The preparation method of the silicon-carbon composite material of this embodiment is different from the preparation method of Example 11 only in that: this embodiment adds step 4) on the basis of Example 11): the coconut shell activated carbon after silicon deposition in step 3) is returned to step 2), and steps 2) to 3) are repeated 10 times. The contents not mentioned are the same as those in Example 11.

[0045] 2. Examples of Silicon Carbon Composite Materials The silicon-carbon composite material of this embodiment is prepared by using the preparation method of any one of the above embodiments 1-13, which will not be described in detail here.

[0046] 3. Examples of Lithium-ion Batteries The lithium-ion battery of this embodiment includes a positive electrode sheet, a separator and a negative electrode sheet. The negative electrode sheet includes a negative electrode collector and a negative electrode active material layer coated on the negative electrode collector. The negative electrode active material in the negative electrode active material layer is a silicon-carbon composite material prepared by the preparation method of any one of the above embodiments 1-13.

[0047] Comparative Example 1 The preparation method of the silicon-carbon composite material of this comparative example comprises the following steps: 1) Place coconut shell activated carbon in a gas-solid reactor and introduce nitrogen to replace the air in the gas-solid reactor until an oxygen-free environment is formed inside the equipment; 2) After the oxygen-free environment is formed, monosilane is introduced into the gas-solid reactor at a flow rate of 10 L / min. At the same time, the gas-solid reactor is heated at a heating rate of 6 °C / min, the heating end point is 750 °C, and the insulation time is 50 h. After cooling, the introduction of monosilane is stopped to prepare a silicon-carbon composite material.

[0048] Comparative Example 2 The preparation method of the silicon-carbon composite material of this comparative example comprises the following steps: 1) Place coconut shell activated carbon in a gas-solid reactor and introduce nitrogen to replace the air in the gas-solid reactor until an oxygen-free environment is formed inside the equipment; 2) After the oxygen-free environment is formed, monosilane is introduced into the gas-solid reactor at a flow rate of 15 L / min. At the same time, the gas-solid reactor is heated at a heating rate of 6°C / min, the heating end point is 750°C, and the insulation time is 10 h. After cooling, the introduction of monosilane is stopped to prepare a silicon-carbon composite material.

[0049] Experimental example The silicon-carbon composite materials prepared in Examples 1 to 13 and Comparative Examples 1 to 2 were used as negative electrode active materials and lithium sheets were used as counter electrodes to assemble button cells for electrochemical performance testing, and their first discharge specific capacity, first efficiency, and capacity retention rate after 300 charge and discharge cycles at a current density of 0.1C and a voltage window of 0.005-2V were tested. All test data are shown in Table 2.

[0050] Table 2 Button battery performance test results sample First discharge specific capacity (mAh / g) First effect (%) Capacity retention after 30 cycles (%) Example 1 1027 88.91 81.43 Example 2 986 81.74 78.92 Example 3 891 86.93 81.28 Example 4 924 88.12 76.24 Example 5 1116 88.96 87.24 Example 6 1194 88.94 89.75 Example 7 1234 89.27 90.21 Example 8 1231 89.24 90.24 Example 9 1378 90.63 90.61 Example 10 1364 89.92 90.45 Embodiment 11 1368 89.25 91.48 Example 12 1392 91.68 91.57 Example 13 1421 90.36 90.64 Comparative Example 1 1293 85.42 83.27 Comparative Example 2 942 86.75 74.64 Comparing the data obtained from the tests of Examples 1 to 4, it can be seen that under the same conditions, the electrochemical performance of the silicon-carbon composite material prepared by using coconut shell activated carbon is better than that of passion fruit shell activated carbon, pecan shell activated carbon and peanut shell activated carbon. This shows that the higher the mesopore ratio of the activated carbon, for example, when the mesopore ratio reaches 25-31%, the more conducive it is to improving the electrochemical performance of the material.

[0051] By comparing the data obtained from the tests of Examples 1, 5 to 6, it can be seen that as the flow rate of silane increases, the prepared silicon-carbon composite material has improved initial discharge capacity and capacity retention rate after 30 cycles, and there is almost no obvious change in the initial efficiency.

[0052] Comparing the data of Examples 6 to 8, it can be seen that when the temperature rises from 600°C to 750°C, the first discharge specific capacity, first efficiency and capacity retention rate after 30 cycles are all improved to a certain extent, but when the temperature rises to 900°C, the data do not change significantly.

[0053] Comparing the data of Example 7 and Implementation 9-10, it can be seen that the more times the porous carbon is introduced, the higher the silicon content adsorbed by the porous carbon, and the greater the contribution to the capacity. When the number of times silane is introduced increases from 1 to 5 times, the first discharge specific capacity, first effect, and capacity retention rate after 30 cycles of the button battery made of the prepared silicon-carbon composite material are improved to a certain extent, but when the number of times silane is introduced increases from 5 to 10 times, its first discharge specific capacity, first effect, and capacity retention rate after 30 cycles are slightly reduced. This may be because the amount of silane that can be carried in the pores reaches the limit value, and the excess silane introduced is adsorbed on the surface of the porous carbon in large quantities, causing direct contact between silicon and the electrolyte, making the SEI film unstable.

[0054] By comparing the data of Example 7 and Example 11, Example 9 and Example 12, and Example 10 and Example 13, it can be seen that the use of disilane as the silicon source gas has better performance than monosilane in terms of first discharge specific capacity, first efficiency, and capacity retention rate after 300 cycles.

[0055] By comparing the test results of Comparative Example 1 with Example 9, and Comparative Example 2 with Example 7, it can be seen that the performance of the silicon-carbon composite material prepared by the preparation method of the present invention is significantly improved compared with the traditional high-temperature silane cracking method preparation process.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: 1) The porous carbon is subjected to adsorption of silane gas in a silane atmosphere at a pressure higher than normal pressure to obtain porous carbon adsorbed with silane; 2) The porous carbon adsorbed with silane is subjected to a heating treatment to decompose the silane gas adsorbed by the porous carbon to generate elemental silicon which is deposited on the porous carbon.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: Step 1) After the adsorption is completed, the adsorption amount of silane gas per 10 kg of porous carbon is at least 110 L; the silane gas is monosilane and / or disilane.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The pressure of the silane atmosphere is 0.2-0.6 MPa.

4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: After a certain amount of silane gas is introduced, the porous carbon is allowed to reach adsorption equilibrium, wherein the pressure at the adsorption equilibrium is 0.2-0.6 MPa.

5. The method for preparing the silicon-carbon composite material according to claim 1 or 2, characterized in that: The BET specific surface area of ​​the porous carbon is 1400-1800 m 2 / g, the average pore size is 2-4nm, and the mesopore ratio is 20-31%.

6. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The porous carbon is fruit shell biomass charcoal; the fruit shell biomass charcoal is one or any combination of coconut shell activated carbon, passion fruit shell activated carbon, pecan shell activated carbon, and peanut shell activated carbon.

7. The method for preparing the silicon-carbon composite material according to claim 1 or 2, characterized in that: The heating treatment is to heat the porous carbon to 600-900° C. for heat preservation treatment.

8. The method for preparing the silicon-carbon composite material according to claim 1 or 2, characterized in that: The method further comprises step 3): returning the porous carbon after the elemental silicon is deposited in step 2) to step 1), and repeating steps 1) and 2) for 2-10 times.

9. A silicon-carbon composite material prepared by the method for preparing a silicon-carbon composite material as claimed in any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery uses the silicon-carbon composite material according to claim 9 as a negative electrode active material.

Citation Information

Patent Citations

  • High-tap-density double-carbon-layer silicon-carbon composite material and preparation method thereof

    CN113193183A

  • Amorphous silicon-carbon composite material, preparation method and application thereof, and lithium ion secondary battery

    CN115995542A

Cited By

  • Nano-silicon-doped porous carbon for silicon-carbon negative electrode, preparation method of nano-silicon-doped porous carbon, silicon-carbon negative electrode material and battery

    CN121180972A

  • Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and battery

    CN121416449A

  • Silicon-carbon negative electrode material, preparation method thereof, negative electrode sheet and battery

    CN121416449B